2009
DOI: 10.5539/ijbm.v4n12p70
|View full text |Cite
|
Sign up to set email alerts
|

Supply Chain Management and Challenges Facing the Food Industry Sector in Tanzania

Abstract: The complexities of food supply chain impose enormous challenges to the processors. As compared to multinational food companies operating in Tanzania, local firms have been performing inefficiently or going out of the business because they could hardly withstand the competition. SCM in the food industry sector was studied in a qualitative survey covered 23 food processing firms in Tanzania, with the purposes of identifying the existing supply chain operation, knowledge of SCM concept and challenges facing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 17 publications
3
17
0
Order By: Relevance
“…Supply chains are often inefficiently long (i.e., they consist of many entities) and disintegrated (i.e., they consist of many small producers selling products to many small customers). Products might also be processed on a primary and secondary basis by small and medium companies [33,34]. Additionally, distribution networks in developing countries are complex and fine-meshed, as products move into multiple distribution layers including traders, wholesalers, and retail stores [35].…”
Section: Discussionmentioning
confidence: 99%
“…Supply chains are often inefficiently long (i.e., they consist of many entities) and disintegrated (i.e., they consist of many small producers selling products to many small customers). Products might also be processed on a primary and secondary basis by small and medium companies [33,34]. Additionally, distribution networks in developing countries are complex and fine-meshed, as products move into multiple distribution layers including traders, wholesalers, and retail stores [35].…”
Section: Discussionmentioning
confidence: 99%
“…Tanzania like any other developing country, agriculture supply chain is facing enormous constraints that affect its sustainability (Ruteri & Xu, 2009). The constraints effect on both side of the spectrum (upward and downward).…”
Section: Supply Chain Constraints Of Dairy Products In Tanzaniamentioning
confidence: 99%
“…On top of that, the qualitative survey analysis by RUTERI AND XU (2009a) found that, small and medium scale food processors in Tanzania suffer from severe exposure to information asymmetries. As such, become constrained from achieving economies of scale and scope.…”
Section: Problem Statement and Objectivesmentioning
confidence: 99%
“…Specifically, food sub-sector of Tanzania is largely made of small scale enterprises and than large scale enterprises (LEs) that supply raw and processed products. All together are centred on processing locally produced agricultural goods (RUTERI AND XU, 2009a). ADJEI ET AL.…”
Section: Introduction Tanzanian Small-scale Enterprises In Generalmentioning
confidence: 99%